DIGITAL TRANSFORMATION IN CONSTRUCTION MANAGEMENT: ASSESSING THE READINESS OF PALESTINIAN COMPANIES - Qabajah, Azmi (An-Najah National University, 2025)
This study investigates the readiness of Palestinian construction companies to adopt digital transformation (DT) using artificial intelligence (AI) tools, while identifying associated challenges and proposing strategic solutions. In light of low productivity and marginal profit margins in the construction sector, DT is seen as a driver for improving project performance and innovation. The study evaluates how strategy, technological infrastructure, and human resources affect DT adoption and examines digital maturity as a mediating factor. A mixed-method approach was adopted. Qualitative data were collected through 13 semi-structured interviews, while quantitative data were obtained via a structured questionnaire distributed to 333 companies, with 143 valid responses (response rate: 42.9%). The Partial Least Squares Structural Equation Modeling (PLS-SEM) technique was used for data analysis. The findings reveal that the level of digital transformation adoption (ADT) was high (mean = 3.73/5), digital maturity (DM) scored a mean of 3.64, while project performance (MP) showed a very high level (mean = 4.18). Among ADT dimensions, technology had the highest influence (mean = 3.96), followed by strategy and human resources (mean = 3.62 each). The structural model showed strong, significant relationships between DT adoption and project performance (R² = 0.712), with digital maturity partially mediating this relationship (VAF = 52%). Key challenges identified include weak digital skills, limited infrastructure, and regulatory constraints. In response, the study proposes a strategic framework that includes: (1) investment in modern digital infrastructure, (2) development of digital competencies, and (3) regulatory reform. These strategies aim to enhance digital adoption and ensure sustainable performance gains in the Palestinian construction sector. This research provides empirical evidence of DT readiness and contributes actionable solutions and policy recommendations to accelerate digitalization in developing construction markets.
التحول الرقمي في إدارة الإنشاءات: 'تقييم جاهزية الشركات الفلسطينية'